Impact of fertilization and tillage practices on transformations of carbon, essential plant nutrients and microbial biota composition in soils: a review - Salwinder Singh Dhaliwal; Arvind Kumar Shukla; Sanjib Kumar Behera; Sarwan Kumar Dubey; Sandeep Sharma; Mehakpreet Kaur Randhawa; Gagandeep Kaur; Sohan Singh walia; Amardeep Singh Toor (Technology in Agronomy)
Soil management approaches have been advocated to modify the soil fertility parameters for higher agricultural production through different land systems. The present review examines the influence of organic/inorganic fertilizers and tillage practices through transformations in regulating the nutrient status, microbial components, and soil organic carbon. Fertilization along with different tillage practices have been found to affect the available plant nutrient content including macronutrients, secondary nutrients, and micronutrients. The review investigation also showed that, compared to inorganic fertilizers (INF), application of compost enhanced plant available macronutrients (N, P, K), micronutrients (Zn, Cu, Fe, Mn) and soil organic carbon (SOC) with different tillage practices. Through different land systems, transformation of the plant available macronutrients, micronutrients and microbial compositions showed their enhancement. Microbial parameters viz. microbial biodiversity, microbial biomass carbon (MBC), potentially mineralizable nitrogen (PMN), microbial biomass nitrogen (MBN) and microbial respiration reported increase. Soil organic carbon and aggregate distribution in the soil and the aggregate-associated organic carbon and physical fractions of SOC have also been reviewed. Among different tillage systems, the reduced tillage with residue incorporation and no-tillage (zero tillage) with residue mulching, significantly enhanced carbon sequestration in soil aggregates in comparison to conventional tillage with residue removal treatments. The practice of zero tillage improved dissolved organic carbon and MBC in light and heavy fractions of carbon in the upper layers of soil.